The Impacts of Intra-Trade on Industrialization: Evidence from COMESA - Yahia, Yassin Elshain; Liu, Haiyun; Sirag, Abdalla; Shah, Sayyed Sadaqat Hussain (Asian Development Policy Review, 2020)
This study examines the impact of intra-export on the industrialization in the Common Market for Eastern and Southern Africa (COMESA) over the period 2000 – 2018. The study used a heterogeneous dynamic Autoregressive Distributed-lag (ARDL), namely Pooled Mean Group (PMG) and Mean Group (MG) estimators. The results reveal that intra-export (lnEXT), internet (lnINT), and Human Development Index (lnHDI) have significant positive effects on the industrialization (lnMVA) in the long-run. The financial development Index (FD) exhibits a significant adverse impact on the lnMVA in the long-run, while only the lnINT confirms a significant adverse impact on the lnMVA in the short-run. The results support the established theoretical framework, particularly the endogenous approach, as well as the supply-side and demand-side capacities. These findings may provide some guidance on policies and strategies harmonization to address the supply-side and demand-side capacities, namely, the infrastructure (e.g. INT), human development and to promote industrialization in the region, ceteris paribus.